2015
DOI: 10.1039/c5fo00500k
|View full text |Cite
|
Sign up to set email alerts
|

Rutin inhibits amylin-induced neurocytotoxicity and oxidative stress

Abstract: Recent evidence showed that amylin deposition is not only found in the pancreas in type 2 diabetes mellitus (T2DM) patients, but also in other peripheral organs, such as kidneys, heart and brain. Circulating amylin oligomers that cross the blood-brain barrier and accumulate in the brain may be an important contributor to diabetic cerebral injury and neurodegeneration. Moreover, increasing epidemiological studies indicate that there is a significant association between T2DM and Alzheimer's disease (AD). Amylin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 67 publications
2
45
0
Order By: Relevance
“…However, the tested concentrations of morin were much lower than those of LAMF or LAMR. The other phytophenols, such as chlorogenic acid, maclurin, rutin, isoquercitrin and luteolin, have been reported to protect cells similarly from oxidative damage by our and other laboratories [15, 18, 2123]. This suggests that phytophenols can be considered as bioactive compounds for the protective effects of LAMF and LAMR, especially morin and maclurin, which can be considered as bioactive and marker compounds.…”
Section: Resultssupporting
confidence: 54%
“…However, the tested concentrations of morin were much lower than those of LAMF or LAMR. The other phytophenols, such as chlorogenic acid, maclurin, rutin, isoquercitrin and luteolin, have been reported to protect cells similarly from oxidative damage by our and other laboratories [15, 18, 2123]. This suggests that phytophenols can be considered as bioactive compounds for the protective effects of LAMF and LAMR, especially morin and maclurin, which can be considered as bioactive and marker compounds.…”
Section: Resultssupporting
confidence: 54%
“…Turgut et al [52] proposed oxidative stress reduction as a major mechanism for the neuroprotective effect of Capparis spinosa L. in D-galactose-induced cognitive impairment. Yu et al [53] demonstrated the neuroprotective role of rutin against amylin-induced neurocytotoxicity in neuronal cells and concluded that the antioxidant property of rutin might have played a role in the protection of neuronal cells. Mairuae et al [54] showed the in vitro neuroprotective effect of okra in SH-SY5Y cells and suggested that the antioxidant effect of okra was responsible for the protective role.…”
Section: Natural Products and Alzheimer's Diseasementioning
confidence: 99%
“…Among the main chemical compounds responsible for the antioxidant activities of medicinal plants, phenolic compounds and flavonoids are the most prominent because of their roles against oxidative stress [20,21]. …”
Section: Introductionmentioning
confidence: 99%